Awareness of Foodborne Pathogens among Students: A Cross-Sectional Study in the Kingdom of Saudi Arabia - Mohammed AL-Mohaithef (International Journal of Food Science)
Food poisoning associated with microbial pathogens causes millions of foodborne disease cases in the Kingdom of Saudi Arabia. Awareness about foodborne pathogens may play a positive role in the reduction of foodborne illnesses. The present cross-sectional study investigates awareness about five major microbial pathogens (Salmonella, Campylobacter, Staphylococcus, Listeria, and Escherichia coli) among university students (n=399) from four major cities in the Kingdom of Saudi Arabia. Multiple logistic regression models were used to predict the determinants of inadequate knowledge. Of the 399 study participants, only 34.5% of students knew the above-mentioned foodborne pathogens. Awareness varied by pathogen, and the variations appeared to be related to age, sex, education, and field of study. In comparison to students in health sciences, students in computer sciences were found to be less knowledgeable about foodborne pathogens (OR: 2.85; 95% CI: 1.36-5.99). Our findings suggest that awareness about microbial pathogens is low among students and is associated with their field of study. Effective education programs about foodborne hazards could help improve students’ awareness of microbial pathogens.